2019
DOI: 10.1142/s2251237319500023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Li2+ Doping on the Structural and Optical Properties of CaO Synthesized by Sol–Gel Process

Abstract: This work proposes the synthesis of nanocrystalline calcium oxide (CaO) pure and doped with di®erent concentrations of lithium (Li 2þ ) ions by sol-gel process. Calcium nitrate (Ca(NO 3 Þ 2 Á4H 2 O; 99.99%) and lithium nitrate (LiNO 3 ; 99.99%) were used as precursors. The synthesized powders were characterized by several techniques such as: UV-Vis transmission spectroscopy, Fourier Transform Infra-red spectroscopy (FT-IR) and X-ray di®raction (XRD). The main objective of this paper is to study the in°uence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The linear part of this curve is extrapolated to zero on the energy axis to get the value of optical band gap. The value of optical band gap thus obtained to be 3.48 eV which is lower than the value (6.26 eV) for bulk CaO but found compatible with the reported results for CaO nanoparticles by different researches [11,19]. This low value of optical band gap may be associated with the presence of Ca(OH) 2 phase in the CaO nanoparticles which provides defect states between the energy gap and reduces the band gap.…”
Section: Optical Characterization Of Cao Nanoparticlessupporting
confidence: 87%
See 1 more Smart Citation
“…The linear part of this curve is extrapolated to zero on the energy axis to get the value of optical band gap. The value of optical band gap thus obtained to be 3.48 eV which is lower than the value (6.26 eV) for bulk CaO but found compatible with the reported results for CaO nanoparticles by different researches [11,19]. This low value of optical band gap may be associated with the presence of Ca(OH) 2 phase in the CaO nanoparticles which provides defect states between the energy gap and reduces the band gap.…”
Section: Optical Characterization Of Cao Nanoparticlessupporting
confidence: 87%
“…It has been reported that solution based chemical methods has excellent tendency to control the size, shape, distribution and other properties of the end products [4]. CaO and Ca(OH) 2 nanoparticles are reported to synthesized by sol-gel method, thermal decomposition, precipitation, hydrothermal, microwave-assisted method, etc., [3,9,[11][12][13][14][15][16][17][18][19]. Among all these methods, direct precipitation is simple, cost-effective, reproductive and rapid technique for nanoparticles synthesis [20][21][22].…”
Section: Introductionmentioning
confidence: 99%